Strategi Pemasaran Pakan Ikan Buatan Berbahan Baku Lokal Daun Kelor Di Gampong Reuleut Timur Kecamatan Muara Batu - Riani Riani; Rachmawati Rusydi; Mainisa Mainisa; Salamah Salamah; Saiful Adhar (Universitas Teuku Umar, 2022)
Moringa leaf-based fish feed is feed that is processed by pond farmers in Gampong Reuleut Timur, Muara Batu District, North Aceh, using Moringa leaf raw materials that have good nutritional content and are in accordance with fish needs. This feed is relatively cheap with protein content that meets the needs of fish. However, the feed has not been able to reach a wide market. This is due to the lack of knowledge of farmers about marketing strategies. The service team, through community service activities, aims to provide counseling about marketing strategies for artificial fish feed. Service activities were carried out in Gampong Reuleut Timur, Muara Batu District, North Aceh Regency. Extension activities were carried out by presenting material on the 4P marketing strategy, namely product, price, place, and promotion, and distributing questionnaires to participants to evaluate their understanding of the material. The result of this activity is the increased understanding and knowledge of partners about the 4P marketing strategy, with the hope that later it will be applied to the business that has been occupied in order to obtain maximum profit.<img src=